L’enseignement relatif aux religions en Suisse francophone et dans le canton de Vaud au prisme de la diversité religieuse et non religieuse - Nicole Durisch Gauthier (Cahiers de la Recherche sur l'Education et les Savoirs)
Like other Western European countries, Switzerland is marked by processes of pluralisation and secularisation that are manifested in an increase in religious diversity in society and school and a growing number of people declaring no religious affiliation. These changes also have an impact on schools in French-speaking Switzerland, where teaching about religions has remained a cantonal specificity. Through an analysis of the legal texts of the last decade and a series of interviews with eight novice teachers from the Canton of Vaud, this article aims to analyse how diversity is conceived and practised. The approach through religious and non-religious diversity will also make it possible to identify the disciplinary matrices in which teaching about religions is anchored in French-speaking Switzerland and to put forward didactic pathways attentive to the mechanisms of essentialisation and identity assignment identified in sociology.